2017
DOI: 10.3390/nano7070169
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Self-Assembled Behavior of pH-Responsive Chiral Liquid Crystal Amphiphilic Copolymers Based on Diosgenyl-Functionalized Aliphatic Polycarbonate

Abstract: The morphological control of polymer micellar aggregates is an important issue in applications such as nanomedicine and material science. Stimuli responsive soft materials have attracted significant attention for their well-controlled morphologies. However, despite extensive studies, it is still a challenge to prepare nanoscale assemblies with responsive behaviors. Herein, a new chiral liquid crystal (LC) aliphatic polycarbonate with side chain bearing diosgenyl mesogen, named mPEG43-PMCC25-P(MCC-DHO)15, was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Depending on the percentage of the LC content, the disks displayed a unique ability to stack perpendicular to the major axis in a process driven by the narrow polydispersity (PD) of the copolymer chains, combined with the liquid crystalline order as a driving force. The morphology of BCP nano-objects as a function of pH was investigated by Guo et al [41]. for a diosgenyl functionalised block copolymer, mPEG 43 -PMCC 25 -P(MCC-DHO) 1 .…”
Section: Applications Of Sterol-based Liquid Crystalline Block Copoly...mentioning
confidence: 99%
“…Depending on the percentage of the LC content, the disks displayed a unique ability to stack perpendicular to the major axis in a process driven by the narrow polydispersity (PD) of the copolymer chains, combined with the liquid crystalline order as a driving force. The morphology of BCP nano-objects as a function of pH was investigated by Guo et al [41]. for a diosgenyl functionalised block copolymer, mPEG 43 -PMCC 25 -P(MCC-DHO) 1 .…”
Section: Applications Of Sterol-based Liquid Crystalline Block Copoly...mentioning
confidence: 99%
“…For the synthesis, different bases and solvents were tested at different temperatures (Table 1). Cholesterol and cholestanol moieties were selected as molecular targets because of the thermodynamic affinity of cholesterol for cell membranes and its ability to change its properties, for example by improving their mechanical durability and reducing passive permeability [35][36][37][38][39][40]; another advantage for cholestanes is their rigidity, a useful characteristic in nanoarchitecture. The short-branched hydrocarbon tail confers to cholesterol a high hydrophobic structure, while the polar 3β-hydroxyl group provides a slight amphiphilic nature.…”
Section: Synthesis and Purification Of Bisteroidal Estersmentioning
confidence: 99%
“…For instance, chiral liquid crystals can arrange themselves in highly ordered helical structures because of the twisting power of chiral molecules . In particular, chiral LCPs are promising candidates for stimuli-responsive materials because they undergo sharp changes in their highly ordered helical structures under external stimuli, such as changes in temperature, , pH, and biomolecules, similar to biological membranes. However, few studies have reported the use of thermotropic LCPs for medical applications such as drug delivery systems (DDSs) and biosensors.…”
Section: Introductionmentioning
confidence: 99%